HUBUNGAN MUTU PELAYANAN KESEHATAN DENGAN TINGKAT KEPUASAN PASIEN RAWAT INAP DI PUSKESMAS AMPIBABO KABUPATEN PATIGI MOUTONG - Nurhasni, Nurhasni (Katalogis, 2018)
The district Ampibabo Parigi Moutong is one puskesmas providing services for inpatient or outpatient treatment, and is implementing units district health offices parigi, so the quality of health services at community ampibabo must be guaranteed to meet the needs of patients and can give satisfaction patients. The aims to understand the relationship the quality of health services the level of satisfaction in patient treatment at puskesmas ampibabo. Based on analysis univariat and bevariat that are analyzed from the answers respondents visits inpatients years 2016 (agustus-november) about the results 64 the that (1) the quality of health services in terms of the level of satisfaction based on the reliability of patients at puskesmas ampibabo district Parigi Moutong less than half respondents are sure, (2) the quality of health services in terms of the level of satisfaction based on dimensions responsiveness patients at puskesmas ampibabo district parigi moutong more than half of respondents said good enough, (3) the quality of health services in terms of the satisfaction of assurance based on dimension patients at puskesmas Ampibabo district parigi moutong more than half of respondents said good enough, (4) quality health pelayanann in terms of the satisfaction of empathy based on dimension patients at puskesmas Ampibabo district Parigi Moutong most stated good enough, (5) the quality of health services in terms of it.